Avaliação bilateral da cinemática linear e da ativação muscular durante o alcance com estímulo funcional em indivíduos hemiparéticos crônicos - Salazar, Luisa Fernanda Garcia (2015)
One of the major clinical problems of post-stroke people is regarding the loss of upper limb function, which impairs daily activities performance, especially those involving reaching. Increased muscle tone, sensory deficits and weakness are alterations that affect both muscle activation pattern and movement strategies of upper limb during reaching. The performance of specific functional tasks during the rehabilitation process must occur within enriched contexts. The implementation of useful objects has been recommended for reach facilitation. Objective: To describe movement strategies and bilateral muscle activation during reaching an object with functional utility in chronic hemiparetic subjects. Methods: Fifteen ischemic post-stroke subjects and 15 healthy subjects matched for age and gender were included in the study. During a task of touching a glass of water and/or a black cylinder were obtained the following variables in a synchronized way: a) electromyographic: magnitude of muscular activity of superior trapezius, pectoral major, biceps brachii, triceps brachii, serratus anterior, anterior deltoid and middle deltoid of both sides; and b) kinematics: peak velocity, percentage of time to reach peak velocity, trajectory, reach path ratio, movement time, and trunk displacement during a reaching task. Results: There was effect of the functional utility of objects neither in movement strategies, nor in muscle activation of both upper limbs in hemiparetic and control subjects. A reduction in the magnitude of electromyographic signal was observed in both upper limbs of hemiparetic subjects in the anterior deltoid and upper trapezius muscles, while the brachial biceps and pectoral major were increased compared to healthy subjects. The triceps braquii muscle showed an increase magnitude in the non-paretic limb when compared to the paretic limb and upper limb of healthy subjects. Changes in upper limb muscle activation which did not perform the movement were also identified. Both paretic and non-paretic limbs showed higher movement time, and trunk anterior displacement, as weel as, and lower peak velocity and reach path ratio during the transport phase, compared to the upper limb of healthy subjects. Conclusion: Subjects with chronic hemiparesis presented bilateral changes in muscle activation and in movement strategies during reaching. The compensatory strategies generated by these subjects did not seem to be affected by the functional utility of the objects in controlled environments.